Copper Inhibits the AlkB Family DNA Repair Enzymes under Wilson’s Disease Condition - Bian, Ke (Chem Res Toxicol, 2017)
Disturbed metabolism of copper ions can cause diseases such as Wilson’s disease (WD). In this work, we investigated the inhibitory effect of Cu(II) ion in vitro on the AlkB family DNA repair enzymes, which are members of the Fe(II)/alpha-ketoglutarate-dependent dioxygenase and include human ALKBH2, ALKBH3, and E. coli AlkB proteins. None of the three proteins was significantly inhibited under normal cellular copper concentrations. However, under WD related condition, we observed that the activities of all three enzymes were strongly suppressed (from 95.2 to 100.0%). We also noted the repair efficiency under ds-DNA condition was less susceptible than ss-DNA to the inhibition.